Understanding the effect of stay-at-home orders on psychological distress during the COVID-19 pandemic: Evidence from a longitudinal study in Australia - Patrick Rehill; Roy Barnes; Nicholas Biddle; Ben Edwards (PLoS ONE, 2025)
The extraordinary public policy response to COVID-19 in Australia saw extended lockdowns in some Australian states and territories, some of the longest in the world. This paper seeks to understand the effect these periods of lockdown had on the mental health of those living through them. Using a staggered difference-in-differences design we study two different periods — one in 2020, one in 2021. During this time there were some jurisdictions (Victoria, New South Wales and in the second period the Australian Capital Territory) experiencing extended lockdowns while the rest of the country was largely living life as normal with no or low local transmission of the virus. While there seems to have been an effect in this first period, we do not find a statistically measurable effect in 2021 as even though distress rose during the lockdown period, it rose similarly among those jurisdictions out of lockdown as well. We speculate this may be because of adaptation to stress, growing cases in control jurisdictions, or the vaccine roll-out providing a concrete endpoint for lockdowns.